2016
DOI: 10.1016/j.adro.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of late radiation damage on left atrial fibrosis using cardiac late gadolinium enhancement magnetic resonance imaging

Abstract: PurposeThis is a proof-of-principle study investigating the feasibility of using late gadolinium enhancement magnetic resonance imaging (LGE-MRI) to detect left atrium (LA) radiation damage.Methods and materialsLGE-MRI data were acquired for 7 patients with previous external beam radiation therapy (EBRT) histories. The enhancement in LA scar was delineated and fused to the computed tomography images used in dose calculation for radiation therapy. Dosimetric and normal tissue complication probability analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
5
12
1
Order By: Relevance
“…On our review, the current study is one of only few to evaluate LGE and T1 mapping sequences in the detection of diffuse left ventricular fibrosis secondary to radiotherapy. Our analysis on LGE most similarly parallels the recently published manuscript by Huang et al [38] In Huang et al, 7 patients with previous thoracic radiotherapy with median time from treatment to CMR of 3.1 years exhibited a linear relationship between EQD2 Dmean and Dmax doses delivered to the left atrium and right atrium and the fibrosis volume on CMR. Interestingly, however, they did not observe any focal left or right ventricle myocardial fibrosis, and did not see a dose relationship within the right atrium scar volume [38].…”
Section: Discussionsupporting
confidence: 86%
“…On our review, the current study is one of only few to evaluate LGE and T1 mapping sequences in the detection of diffuse left ventricular fibrosis secondary to radiotherapy. Our analysis on LGE most similarly parallels the recently published manuscript by Huang et al [38] In Huang et al, 7 patients with previous thoracic radiotherapy with median time from treatment to CMR of 3.1 years exhibited a linear relationship between EQD2 Dmean and Dmax doses delivered to the left atrium and right atrium and the fibrosis volume on CMR. Interestingly, however, they did not observe any focal left or right ventricle myocardial fibrosis, and did not see a dose relationship within the right atrium scar volume [38].…”
Section: Discussionsupporting
confidence: 86%
“…On our review, the current study is one of only few to evaluate LGE and T1 mapping sequences in the detection of diffuse left ventricular fibrosis secondary to radiotherapy. Our analysis on LGE most similarly parallels the recently published manuscript by Huang et al [38] In Huang et al, 7 patients with previous thoracic radiotherapy with median time from treatment to CMR of 3.1 years exhibited a linear relationship between EQD2 Dmean and Dmax doses delivered to the left atrium and right atrium and the fibrosis volume on CMR. Interestingly, however, they did not observe any focal left or right ventricle myocardial fibrosis, and did not see a dose relationship within the right atrium scar volume.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, however, they did not observe any focal left or right ventricle myocardial fibrosis, and did not see a dose relationship within the right atrium scar volume. [38] In our LGE protocol, no images of the right or left atria were acquired as atrial walls are generally thin and reliable LGE measurement is therefore difficult. Interestingly, despite higher prescription doses in our study no dose effect was identified for LGE.…”
Section: Discussionmentioning
confidence: 99%
“…There was a trend towards higher T1 values in patients with evidence of LGE, which likely shows the effect of local brosis changes on mean T1 values obtained from larger volumes.On our review, the current study is one of only few to evaluate LGE and T1 mapping sequences in the detection of diffuse left ventricular brosis secondary to radiotherapy. Our analysis on LGE most similarly parallels the recently published manuscript by Huang et al[38] In Huang et al, 7 patients with previous thoracic radiotherapy with median time from treatment to CMR of 3.1 years exhibited a linear relationship between EQD2 Dmean and Dmax doses delivered to the left atrium and right atrium and the brosis volume on CMR. Interestingly, however, they did not observe any focal left or right ventricle myocardial brosis, and did not see a dose relationship within the right atrium scar volume [38].…”
supporting
confidence: 86%
“…Our analysis on LGE most similarly parallels the recently published manuscript by Huang et al[38] In Huang et al, 7 patients with previous thoracic radiotherapy with median time from treatment to CMR of 3.1 years exhibited a linear relationship between EQD2 Dmean and Dmax doses delivered to the left atrium and right atrium and the brosis volume on CMR. Interestingly, however, they did not observe any focal left or right ventricle myocardial brosis, and did not see a dose relationship within the right atrium scar volume [38]. In our LGE protocol, no images of the right or left atria were acquired as atrial walls are generally thin and reliable LGE measurement is therefore di cult.…”
supporting
confidence: 86%